Feedback on Students' Performance: Possible Ways of Enhancing Students' Success with Formative Assessment - Delia Muste; Tamari Ivanidze (Babes-Bolyai University, 2023)
Feedback has become as the main performance metric that's why meaningful and thoughtful feedback is important for improving students' learning path. It is provided by teachers to close the students' knowledge gap. Positive outcomes are determined by informative, goal-oriented and friendly delivered feedback. However, students and teachers lack knowledge about the role of feedback and its contribution in learners' progress. This article delves the significance of feedback on students' performance and its role for students' enhanced learning. The paper presents different types of formative feedback and their effectiveness for students' performance improvement. It also shows how effective feedback works in the classroom and strategic choices for feedback implementation. Feedback is presented as an essential tool for improving quality of teaching and education in general.